Perjanjian Kerja Untuk Waktu Tertentu (Perjanjian Kerja Kontrak) Perlu Ditertibkan - Rusli, Hardijan (LAW REVIEW, 2002)
The Indonesian employment law for limited period does not provide a probationary period Â for new employees. This means that under employment contract for limited period may not be a probationary period clause but the employment contract for an unlimited periode may have the clause. This probationary period allows time for adjustment on the job and an opportunity for the employee and employer to determine whether the employment relationship should continue. At any point during the probationary period an employer may dismiss employee from employment without cause and the employer too, can be dimissed by the employee. Probationary period will last for three months. After probationary period the employee should be contracted for an unlimited period not a limited period. But many employers put probationary period under employment contract for limited period. This act actually is illegal, ignorant and also arrogant.